Disentangling Within- and Between-Person Effects During Response Inhibition in Obsessive-Compulsive Disorder - Hagland, Pernille; Thorsen, Anders Lillevik; Ousdal, Olga Therese; Gjestad, Rolf; de Wit, Stella J.; Hansen, Bjarne; Hagen, Kristen; Kvale, Gerd; van den Heuvel, Odile A. (Frontiers in Psychiatry, 2021)
Background Obsessive-compulsive disorder (OCD) has been related to worse performance, abnormal brain activity and functional connectivity during response inhibition. Whether these findings are indications of stable traits that contribute to the development of the disorder, or whether they are a result of the state severity of obsessions and anxiety, remains unclear since previous research mainly has employed cross-sectional designs. The present study aimed to assess longitudinal between- and within-person relationships between symptoms, task performance, right inferior frontal gyrus brain activation, and connectivity between the right amygdala and the right pre-supplementary motor area in 29 OCD patients before and after concentrated exposure and response prevention treatment. Method Patients received exposure and response prevention delivered during four consecutive days, following the Bergen 4-day Treatment format. Patients performed a Stop Signal Task during 3T functional Magnetic Resonance Imaging the day before treatment, as well as one week and three months after treatment completion. Multilevel models were used to analyze disaggregated within- and between-person effects over time. Independent variables were scores on the symptom severity scales for OCD, anxiety, depression, and state distress during scanning. Dependent variables were reaction time for go trials, stop signal response time, task-related brain activation and connectivity. Results A positive between-person effect was found for obsessive-compulsive, anxiety and depressive symptom severity on go trial reaction time, indicating that patients with higher symptom scores on average respond slower during accurate go trials. We also found no significant between- or within-person relations between symptom severity and task-related activation or fronto-limbic connectivity. Conclusions The between-person findings may point toward a general association between slower processing speed and symptom severity in OCD. Longitudinal studies should disaggregate between- and within-person effects to better understand variation over time.